Variasi Kosentrasi Cuka Apel terhadap Daya Hambat Pertumbuhan Escherichia coli dan Staphylococcus aureus - Rasmi, Kadek Anidia; Aryasa, I Wayan Tanjung; Laksmita, Ayu Saka (Bali International Scientific Forum, 2023)
Background: Apple cider vinegar is a fermentation of apple cider which contains various compounds that are beneficial for health. Such can be useful as an antibacterial due to the content of acetic acid, gallic acid, and catechins. Purpose: This study aims to determine the effect of variations in the concentration of apple cider vinegar and the most effective concentration of apple cider vinegar in inhibiting the growth of Escherichia coli and Staphylococcus aureus in vitro. Method: The method used in this study is a quasi experimental with disc diffusion for antibacterial testing. In this study, four concentrations of apple cider vinegar were used, that are 100%, 75%, 50%, and 25%. Result: The results of the antibacterial activity test on Escherichia coli showed the average diameter of the inhibition zone, i.e. 12.33 ± 0.12 mm (strong category) for concentration 100%, 10.57 ± 0.20 mm (strong category) for concentration 75%, 6.52 ± 0.22 mm (medium category) for concentration 50%, and 2.56 ± 0.18 mm (weak category) for concentration 25%. Whereas Staphylococcus aureus showed the average diameter of the inhibition, i.e. 14,56 ± 0,46 mm (strong category) for concentration 100%, 12,60 ± 0,07 mm (strong category) for concentration 75%, 8,62 ± 0,04 mm (medium category) for concentration 50%, and 4,54 ± 0,12 mm (weak category) for concentration 25%. Conclusion: Apple cider vinegar concentrations of 75% and 100% were effective in inhibiting the growth of the two test bacteria because they showed inhibition with strong category. Keywords: apple cider vinegar, Escherichia coli, Staphylococcus aureus.